Role of Cathepsin S in Periodontal Inflammation and Infection. (6th December 2017) - Memmert, S.; Damanaki, A.; Nogueira, A. V. B.; Eick, S.; Nokhbehsaim, M.; Papadopoulou, A. K.; Till, A.; Rath, B.; Jepsen, S.; Götz, W.; Piperi, C.; Basdra, E. K.; et al.
Abstract : Cathepsin S is a cysteine protease and regulator of autophagy with possible involvement in periodontitis. The objective of this study was to investigate whether cathepsin S is involved in the pathogenesis of periodontal diseases. Human periodontal fibroblasts were cultured under inflammatory and infectious conditions elicited by interleukin-1 β and Fusobacterium nucleatum, respectively. An array-based approach was used to analyze differential expression of autophagy-associated genes. Cathepsin S was upregulated most strongly and thus further studied in vitro at gene and protein levels. In vivo, gingival tissue biopsies from rats with ligature-induced periodontitis and from periodontitis patients were also analyzed at transcriptional and protein levels. Multiple gene expression changes due to interleukin-1 β and F. nucleatum were observed in vitro . Both stimulants caused a significant cathepsin S upregulation. A significantly elevated cathepsin S expression in gingival biopsies from rats with experimental periodontitis was found in vivo, as compared to that from control. Gingival biopsies from periodontitis patients showed a significantly higher cathepsin S expression than those from healthy gingiva. Our findings provide original evidence that cathepsin S is increased in periodontal cells and tissues under inflammatory and infectious conditions, suggesting a critical role of this autophagy-associated molecule in the pathogenesis of periodontitis.